Philosophy 167: Class 5 - Part 3 - Galileo: Biography (1564-1616). - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Describes the early part of Galileo's life, up until De revolutionibus is put on the index by the inquisition.; Opening line: "This is his life up to a key event, March 3rd, 1616."; Duration: 9:25 minutes.; Segment: Class 5, Part 3.